Blueprint : Ecorack Enterprise (Pallet-Rack For Fertilizer) / Siti Sarah Mohd Sabri - Mohd Sabri, Siti Sarah (2020)
A new product called Pallet-Rack for Fertilizer has been produced to store many fertilizers safely and also to market the product. Pallet-Rack means that the racks are made from pallet which is recyclable and durable. This product may help to reduce the burden in storing the fertilizer and protect the quality of it at the same time. Protected quality of the fertilizers can enhance the growth of the plants.